Demokrasi dalam Bingkal Digital - Sasmita, Siska (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2011)
This article will discuss about democracy in digital framework. Transition in information technology and communications contribute to the existence of democracy in many countries. In developed countries, the virtual space becomes a new means of representing identity and participate in the political sphere. In addition to bridging the distance, the virtual space accommodate more voice and interests.Kata Kunci: Demokrasi, bingkal digital, teknologi informasi, political sphere